Drug Repurposing: In vitro and in vivo Antimicrobial and Antibiofilm Effects of Bithionol Against Enterococcus faecalis and Enterococcus faecium - She, Pengfei; Wang, Yangxia; Li, Yingjia; Zhou, Linying; Li, Shijia; Zeng, Xianghai; Liu, Yaqian; Xu, Lanlan; Wu, Yong (Frontiers in Microbiology, 2021)
Widespread antibiotic resistance has been reported in Enterococci-pathogens that cause life-threatening infections. Antibiotic development has not kept pace with the rapid increase in resistance in Enterococci. Drug repurposing is a promising approach to solve this problem. Bithionol (BT) is a clinically approved anthelminthic drug. In this study, we found that BT showed significant antimicrobial and antibiofilm effects against Enterococcus faecalis and vancomycin-resistant E. faecium in vitro in a dose-dependent manner by disrupting the integrity of bacterial cell membranes. Moreover, BT effectively reduced the bacterial load of mouse organs when combined with conventional antibiotics in a peritonitis infection model. Thus, BT has shown potential as a therapeutic agent for E. faecalis- and vancomycin-resistant E. faecium-related infections.